Dakwah Ekoteologi Islam Ustadz Abdul Somad di Platfrom Youtube "Upaya Melestarikan Lingkungan" - Duirohma Tunjanah; Khusnul Khotimah; Mustain Mustain (Hikmah, 2025)
This research aims to analyze the values of Islamic ecotheology in the sermons of Ustadz Abdul Somad on the YouTube platform as an effort to preserve the environment. A descriptive qualitative approach was chosen to understand the meaning and context of the da'wah messages related to environmental issues. This type of research is a case study focusing on the content analysis of relevant sermon narratives. Data collection techniques were carried out through documentation and non-participatory observation of one of Ustadz Abdul Somad's da'wah contents that discusses environmental da'wah. The data were analyzed using semiotics discourse analysis methods based on the theory of Ferdinand de Saussure, which divides signs into two main elements: signifier and signified. The analysis steps include identifying the signifier, determining the signified, linking signs, and contextualizing the meanings into the frame of Islamic ecotheology. The validity of the data was tested through triangulation techniques of sources and theories. The research results show that the sermons of Ustadz Abdul Somad contain a message of da'wah that views environmental preservation as an integral part of the teachings of Islam, which relates not only to ritual aspects, but also to the moral responsibility of humanity as stewards on earth. The analysis results indicate that the use of the term 'Jannah' (heaven), warnings against deforestation, and invitations to plant trees as acts of charity carry profound ecological meanings that are relevant to contemporary environmental issues. UAS's da'wah integrates spiritual messages with ecological responsibilities, thereby forming a collective awareness among Muslims to preserve nature as part of their devotion to Allah SWT.